High-strength conductive nano lamellar structure Cu-Ti alloy and preparation method thereof
Through vacuum smelting, solid solution treatment and two-step aging treatment, a high-strength conductive nanosheet structure Cu-Ti alloy was prepared, which solved the problem of insufficient conductivity and strength of the existing Cu-Ti alloy, achieved the comprehensive performance of high strength and good conductivity, and the process was simple and suitable for large-scale production.
Patent Information
- Application Number
- CN202510091535.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The existing Cu-Ti alloys have shortcomings in conductivity and strength, and the production process is complex, so they are not suitable for large-scale production.
The alloy ingot was prepared by vacuum smelting, solid solution treatment and two-step aging treatment, forming a nanosheet layered Ti precipitation phase, and combining cold rolling deformation, a high-strength conductive nanosheet layer structure Cu-Ti alloy was prepared.
The alloy has high strength and good conductivity, tensile strength greater than 1000MPa, conductivity greater than 20% IACS, hardness greater than 281HV, and short process flow and simple operation, making it suitable for industrial production.
Smart Images

Figure CN119913392A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of copper alloy processing and relates to a high-strength conductive nanosheet structure Cu-Ti alloy and a preparation method thereof. Background Art
[0002] The rapid development of electronic communications, rail transit and aerospace industries has put forward higher requirements for the comprehensive performance of high-strength conductive materials. Beryllium bronze has excellent mechanical properties, as well as good electrical conductivity, thermal conductivity and corrosion resistance. It is widely used in the fields of electronics, electrical appliances, aerospace, instruments and transportation. It is used to manufacture connectors, elastic elements of relays, vacuum sockets, springs of various control systems, plug-in components, diaphragms, diaphragms, etc. However, due to the poor high-temperature performance of beryllium bronze and the production process that produces toxic substances, it is urgent to develop materials that can replace beryllium copper alloys.
[0003] As an aging-strengthened alloy, Cu-Ti alloy has high strength and elasticity, as well as good heat resistance and fatigue resistance. Its mechanical properties are comparable to those of beryllium copper alloy. In addition, titanium has abundant reserves worldwide and no toxic substances are produced during the production process. Therefore, Cu-Ti alloy is expected to become one of the alternative materials to beryllium copper alloy.
[0004] After proper aging treatment, Cu-Ti alloy can obtain higher strength by spindle decomposition precipitation of nano-coherent strengthening phase, but due to the influence of solid solution Ti atoms on alloy electron scattering, Cu-Ti alloy has low conductivity. Chinese patent with publication number CN117947313A discloses a high-strength conductive Cu-Ti-Ni-Mg alloy and its preparation method, and the conductivity of the plate prepared by the method can reach 32.2-40.1% IACS, but the strength is low, less than 600MPa. Chinese patent with publication number CN114150123A discloses a method for effectively improving the strength and conductivity of the alloy, through composition design, melting and casting, homogenization, low-temperature hot rolling, multiple cycles of ultra-low temperature cold rolling, short-time solid solution quenching, low-temperature short-time pre-aging treatment, multiple cycles of ultra-low temperature deep cold rolling and isothermal aging multi-process integrated coupling control scheme, a Cu-Ti alloy plate with a strength greater than 1000MPa and a conductivity greater than 15% IACS is prepared, but the scheme is complicated to operate and has a long process flow, which is not conducive to large-scale production. Therefore, there is an urgent need to develop a Cu-Ti alloy and a preparation method thereof with excellent comprehensive properties and simple production process to meet the requirements of modern electronics, automobiles and other industries for high-strength conductive materials. Summary of the invention
[0005] The present invention aims at solving the problems in the prior art and provides a high-strength conductive nanosheet structure Cu-Ti alloy and a preparation method thereof. The nanosheet structure Cu-Ti alloy of the present invention has high strength and good conductivity, and has a short process flow and is easy to operate.
[0006] The present invention is achieved through the following technical solutions:
[0007] The invention provides a high-strength conductive nanosheet structure Cu-Ti alloy, which consists of the following components: Ti 2wt.%-5wt.%, the balance being Cu and inevitable impurities, a large amount of nanosheet layered Ti precipitation phases in the Cu matrix, a tensile strength greater than 1000MPa, a conductivity greater than 20%IACS, and a hardness greater than 281HV.
[0008] Furthermore, the Cu-Ti alloy has an electrical conductivity of 20.1% IACS-30.7% IACS, a tensile strength of 1002 MPa-1285 MPa, and a hardness of 281.5 HV-342 HV.
[0009] The present invention also provides a method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy, comprising the following steps:
[0010] (1) preparing alloy ingots by vacuum melting;
[0011] (2) Solution treatment;
[0012] (3) Two-step long-term treatment;
[0013] (4) Cold rolling.
[0014] Furthermore, a method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy also includes step (5) low-temperature short-time aging treatment.
[0015] Furthermore, in step (1), according to the alloy design composition: Ti 2wt.%-5wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace.
[0016] Furthermore, in step (2), the alloy ingot is first milled and then subjected to solution quenching treatment, the solution temperature is 850°C-950°C, the solution time is 1h-4h, and the quenching method is water quenching.
[0017] Furthermore, step (3) is divided into a first long aging treatment and a second long aging treatment, the first long aging treatment temperature is 450°C-600°C, the holding time is 5h-15h, the second long aging treatment temperature is 350°C-450°C, the holding time is 10h-20h, and after the two-step long aging treatment, the average lamella thickness of the nanosheet lamellar Ti precipitation phase in the Cu matrix is 58.6nm-211.3nm, and the average lamella spacing is 97.2nm-605.7nm.
[0018] Furthermore, step (4) is room temperature cold rolling deformation, and the cold rolling reduction rate is 80%-98%.
[0019] Furthermore, in step (5), the low-temperature short-time aging treatment temperature is 250°C-400°C, and the insulation time is 0.5h-2h.
[0020] The invention provides an application of a high-strength conductive nanosheet structure Cu-Ti alloy, which is used as a high-strength conductive material in the fields of electronic communications, rail transportation and aerospace.
[0021] Advantages and effects of the present invention:
[0022] The high-strength conductive nanosheet structure Cu-Ti alloy provided by the present invention does not contain beryllium, thereby avoiding the harmful effects of beryllium on the environment during the production process; the Cu-Ti alloy of the present invention has good electrical conductivity and strength, and has excellent comprehensive performance, with a strength greater than 1000MPa, a conductivity greater than 20%IACS, and a maximum electrical conductivity of 30.7%IACS, at which time the strength is 1050MPa, and a maximum strength of 1285MPa, at which time the electrical conductivity is 20.4%IACS, and the comprehensive performance is good; in the preparation process of the high-strength conductive nanosheet structure Cu-Ti alloy, the present invention selects a two-step long aging treatment for the solid solution alloy, so that The Ti dissolved in the Cu matrix is fully precipitated. During the long-aging treatment, a large number of granular rod-shaped precipitation phases are first generated in the copper matrix. As the aging progresses, the granular rod-shaped precipitation phases gradually transform into lamellar precipitation phases, with an average lamellar thickness of 58.6nm-211.3nm and an average lamellar spacing of 97.2nm-605.7nm. A large number of nano-lamellar Cu4Ti precipitation phases can effectively hinder dislocation movement, increase dislocation density, and enhance the work hardening effect. At the same time, these lamellar precipitation phases can effectively restrain the deformation of the Cu matrix and refine its structure during the subsequent cold rolling process, thereby greatly strengthening the Cu matrix and ultimately significantly improving the strength of the alloy. Over-aging treatment greatly reduces the Ti content in the Cu matrix, and the spacing between the formed lamellar precipitation phases is greater than the electron free path of Cu 45nm, which effectively reduces the influence of Ti on electron scattering, so that the alloy has a higher conductivity while maintaining high strength. The preparation method provided by the present invention has a short process flow and is simple to operate, providing a practical method for large-scale production of high-strength conductive copper alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope (SEM) image of the Cu-3Ti alloy in the long-aging treatment state during the preparation process of Example 1;
[0024] Figure 2 This is a scanning electron microscope (SEM) image of the cold rolling deformation of the Cu-3Ti alloy after long-aging treatment during the preparation process of Example 1;
[0025] Figure 3 This is a scanning electron microscope (SEM) image of the Cu-4Ti alloy in the long-aging treatment state during the preparation process of Example 2;
[0026] Figure 4 This is a scanning electron microscope (SEM) image of the cold rolling deformation of the Cu-4Ti alloy after long-aging treatment during the preparation process of Example 2. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to the embodiments.
[0028] Example 1
[0029] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 3wt.%, and the remainder is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 24.6% IACS, the tensile strength is 1020 MPa, and the hardness is 288.9 HV.
[0030] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0031] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 3wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0032] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2 h.
[0033] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0034] (4) Cold rolling: cold rolling deformation at room temperature with a rolling reduction rate of 90% to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0035] like Figure 1 As shown in the SEM image of the long-aging treatment state during the preparation process of the high-strength conductive nanosheet structure Cu-Ti alloy in this embodiment, a large number of nanosheet layered Cu4Ti precipitation phases can be seen, and the nanosheet layered precipitation phase can effectively improve the strength of the alloy; Figure 2 As shown, the cold rolling deformation SEM image of the high-strength conductive nanosheet structure Cu-Ti alloy in the preparation process of this embodiment shows that the lamellar Cu4Ti precipitated phase is deformed into a fiber shape.
[0036] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 24.6% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1020MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 288.9HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 168.2nm, and the average lamella spacing was 472.9nm.
[0037] Example 2
[0038] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 4wt.%, and the remainder is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 20.1% IACS, the tensile strength is 1155 MPa, and the hardness is 295.1 HV.
[0039] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0040] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 4wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0041] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0042] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0043] (4) Cold rolling: cold rolling deformation at room temperature with a rolling reduction rate of 90% to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0044] like Figure 3 As shown in the SEM image of the long-term aging treatment state during the preparation process of the high-strength conductive nanosheet structure Cu-Ti alloy in this embodiment, a large number of nanosheet layered Cu4Ti precipitation phases can be seen; Figure 4As shown, the cold rolling deformation SEM image of the high-strength conductive nanosheet structure Cu-Ti alloy in the preparation process of this embodiment shows that the lamellar Cu4Ti precipitated phase is deformed into a fiber shape.
[0045] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 20.1% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1155MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 295.1HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 82.5nm, and the average lamella spacing was 144.5nm.
[0046] Example 3
[0047] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 3wt.%, and the remainder is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 28.2% IACS, the tensile strength is 1115 MPa, and the hardness is 323 HV.
[0048] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0049] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 3wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0050] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0051] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0052] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0053] (5) Low temperature short aging treatment: Low temperature short aging treatment was performed at a temperature of 350°C for 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0054] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 28.2% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1115MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 323HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 168.2nm, and the average lamella spacing was 472.9nm.
[0055] Example 4
[0056] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 3wt.%, and the remainder is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 30.7% IACS, the tensile strength is 1050 MPa, and the hardness is 323.3 HV.
[0057] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0058] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 3wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0059] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0060] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0061] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0062] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 400°C and a holding time of 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0063] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 30.7% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1050 MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 323.3 HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 168.2 nm, and the average lamella spacing was 472.9 nm.
[0064] Example 5
[0065] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 4wt.%, and the remainder is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 20.1% IACS, the tensile strength is 1255 MPa, and the hardness is 324.8 HV.
[0066] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0067] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 4wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0068] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0069] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0070] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0071] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 250°C and a holding time of 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0072] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 20.1% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1255MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 324.8HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 82.5nm, and the average lamella spacing was 144.5nm.
[0073] Example 6
[0074] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 3wt.%, and the balance is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 24.8% IACS, the tensile strength is 1100 MPa, and the hardness is 309.1 HV.
[0075] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0076] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 3wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0077] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0078] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0079] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0080] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 250°C and a holding time of 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0081] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 24.8% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1100MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 309.1HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 168.2nm, and the average lamella spacing was 472.9nm.
[0082] Example 7
[0083] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 3wt.%, and the balance is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 25.3% IACS, the tensile strength is 1120 MPa, and the hardness is 310.7 HV.
[0084] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0085] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 3wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0086] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0087] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0088] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0089] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 300°C and a holding time of 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0090] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 25.3% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1120 MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 310.7 HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 168.2 nm, and the average lamella spacing was 472.9 nm.
[0091] Example 8
[0092] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 3wt.%, and the balance is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 26.5% IACS, the tensile strength is 1083 MPa, and the hardness is 310.1 HV.
[0093] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0094] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 3wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0095] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0096] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0097] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0098] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 400°C and a holding time of 0.5 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0099] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 26.5% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1083MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 310.1HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 168.2nm, and the average lamella spacing was 472.9nm.
[0100] Example 9
[0101] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 4wt.%, and the remainder is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 20.3% IACS, the tensile strength is 1240 MPa, and the hardness is 329.8 HV.
[0102] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0103] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 4wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0104] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0105] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0106] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0107] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 300°C and a holding time of 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0108] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 20.3% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1240MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 329.8HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 82.5nm, and the average lamella spacing was 144.5nm.
[0109] Example 10
[0110] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 4wt.%, and the balance is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 22.2% IACS, the tensile strength is 1220 MPa, and the hardness is 324.9 HV.
[0111] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0112] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 4wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0113] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0114] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0115] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0116] (5) Low temperature short aging treatment: Low temperature short aging treatment was performed at a temperature of 350°C for 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0117] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 22.2% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1220MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 324.9HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 82.5nm, and the average lamella spacing was 144.5nm.
[0118] Embodiment 11
[0119] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 4wt.%, and the balance is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 24.3% IACS, the tensile strength is 1100 MPa, and the hardness is 310 HV.
[0120] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0121] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 4wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0122] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0123] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0124] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0125] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 400°C and a holding time of 1 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0126] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 24.3% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1100MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 310HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 82.5nm, and the average lamella spacing was 144.5nm.
[0127] Example 12
[0128] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 4wt.%, and the balance is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 26.7% IACS, the tensile strength is 1045 MPa, and the hardness is 306.3 HV.
[0129] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0130] (1) Preparation of alloy ingot by vacuum melting: According to the designed alloy composition: Ti 4wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace;
[0131] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 900°C, and the solution time is 2h.
[0132] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 550°C for 10 h, and the second long aging treatment is carried out at a temperature of 450°C for 15 h.
[0133] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 90%;
[0134] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 400°C and a holding time of 2h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0135] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 26.7% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1045MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 306.3HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 82.5nm, and the average lamella spacing was 144.5nm.
[0136] Example 13
[0137] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 2wt.%, and the remainder is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 29.8% IACS, the tensile strength is 1002 MPa, and the hardness is 281.5 HV.
[0138] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0139] (1) Preparing alloy ingots by vacuum melting: According to the designed alloy composition: Ti 2wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingots are melted in a vacuum induction furnace;
[0140] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 850°C, and the solution time is 1 h.
[0141] (3) Two-step long aging treatment: the first long aging treatment is carried out at a temperature of 450°C for 15 h, and the second long aging treatment is carried out at a temperature of 400°C for 10 h.
[0142] (4) Cold rolling: cold rolling deformation at room temperature, the rolling reduction rate is 98%;
[0143] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 400°C and a holding time of 0.5 h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0144] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 29.8% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1002MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 281.5HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 211.3nm, and the average lamella spacing was 605.7nm.
[0145] Embodiment 14
[0146] A high-strength conductive nanosheet structure Cu-Ti alloy, wherein the Ti content of the Cu-Ti alloy is 5wt.%, and the balance is Cu and unavoidable impurities, as shown in Table 1, and the electrical conductivity is 20.4% IACS, the tensile strength is 1285 MPa, and the hardness is 342 HV.
[0147] A method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy comprises the following steps:
[0148] (1) Preparing alloy ingots by vacuum melting: According to the designed alloy composition: Ti 5wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingots are melted in a vacuum induction furnace;
[0149] (2) Solution treatment: After milling the alloy ingot, solution quenching treatment is performed at room temperature. The quenching method is water quenching, the solution temperature is 950°C, and the solution time is 4 h.
[0150] (3) Two-step long aging treatment: the second long aging treatment, temperature 600 ° C, holding time 5 h, the third long aging treatment temperature 350 ° C, holding time 20 h;
[0151] (4) Cold rolling: cold rolling deformation at room temperature, with a rolling reduction rate of 80%;
[0152] (5) Low temperature short aging treatment: Low temperature short aging treatment is carried out at a temperature of 400°C and a holding time of 2h to obtain a high-strength conductive nanosheet structure Cu-Ti alloy.
[0153] The conductivity test was measured using a Changzhou Tonghui TH2515 DC resistance tester, and the conductivity of the Cu-Ti alloy prepared in this embodiment was 20.4% IACS; the tensile property test was measured using a Shimadzu AG-XPLUS100KN universal testing machine, and the tensile strength of the Cu-Ti alloy prepared in this embodiment was 1285MPa; the hardness test was measured using a Shanghai Everone MH-500 semi-automatic Vickers hardness tester, and the microscopic Vickers hardness of the Cu-Ti alloy prepared in this embodiment was 342HV; the average lamella thickness of the nanosheet layered Cu4Ti precipitation phase after two-step aging treatment was measured using a Zeiss Auriga Compact FIB-SEM scanning electron microscope, and the average lamella thickness was 58.6nm, and the average lamella spacing was 97.2nm.
[0154] Table 1 Alloy composition and properties of each example
[0155]
[0156] According to Table 1, the nanosheet structure Cu-Ti alloy prepared by the preparation method of a high-strength conductive nanosheet structure Cu-Ti alloy provided by the present invention has high strength and good conductivity, and its tensile strength is greater than 1000MPa, and the conductivity is greater than 20%IACS, and the hardness is greater than 281HV; the tensile strength can reach up to 1285MPa, and the conductivity is 20.4% at this time; the conductivity can reach up to 30.7%IACS, and the tensile strength is 1050MPa at this time; the hardness can reach up to 342HV, and the tensile strength is 1285MPa and the conductivity is 20.4% at this time; the high-strength conductive nanosheet structure Cu-Ti alloy provided by the present invention has excellent comprehensive performance, and the preparation process is short, the operation is simple, and it is conducive to industrial production.
Claims
1. A high-strength conductive nanosheet structure Cu-Ti alloy, characterized in that: The alloy consists of the following components: Ti 2wt.%-5wt.%, the balance being Cu and inevitable impurities, a large amount of nano-sheet layered Ti precipitation phases in the Cu matrix, tensile strength>1000MPa, electrical conductivity>20%IACS, and hardness>281HV.
2. A high-strength conductive nanosheet structure Cu-Ti alloy as claimed in claim 1, characterized in that: The electrical conductivity of Cu-Ti alloy is 20.1% IACS-30.7% IACS, the tensile strength is 1002MPa-1285MPa, and the hardness is 281.5HV-342HV.
3. A method for preparing the high-strength conductive nanosheet structure Cu-Ti alloy according to claim 1, characterized in that: The following steps are involved: (1) preparing alloy ingots by vacuum melting; (2) Solution treatment; (3) Two-step long-term treatment; (4) Cold rolling.
4. The method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy as claimed in claim 3, characterized in that: The method also includes step (5) low temperature short aging treatment.
5. The method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy as claimed in claim 3, characterized in that: Step (1) According to the alloy design composition: Ti 2wt.%-5wt.%, the balance is Cu, 99.9wt% of electrolytic high-purity Cu and sponge Ti are weighed according to the components, and the alloy ingot is melted in a vacuum induction furnace.
6. The method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy as claimed in claim 3, characterized in that: In step (2), the alloy ingot is first milled and then subjected to solution quenching treatment, the solution temperature is 850°C-950°C, the solution time is 1h-4h, and the quenching method is water quenching.
7. The method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy as claimed in claim 3, characterized in that: Step (3) is divided into a first long aging treatment and a second long aging treatment. The first long aging treatment temperature is 450°C-600°C, and the holding time is 5h-15h. The second long aging treatment temperature is 350°C-450°C, and the holding time is 10h-20h. After the two-step long aging treatment, the average lamella thickness of the nanosheet layered Ti precipitation phase in the Cu matrix is 58.6nm-211.3nm, and the average lamella spacing is 97.2nm-605.7nm.
8. The method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy as claimed in claim 3, characterized in that: Step (4) is room temperature cold rolling deformation, and the cold rolling reduction rate is 80%-98%.
9. The method for preparing a high-strength conductive nanosheet structure Cu-Ti alloy as claimed in claim 4, characterized in that: The temperature of step (5) low-temperature short-time aging treatment is 250°C-400°C, and the insulation time is 0.5h-2h.
10. An application of the high-strength conductive nanosheet structure Cu-Ti alloy according to claim 1, characterized in that: Used as high-strength conductive material in electronic communications, rail transportation and aerospace fields.
Citation Information
Patent Citations
Method for effectively improving strength and conductivity of alloy
CN114150123A
High-strength conductive Cu-Ti-Ni-Mg alloy and preparation method thereof
CN117947313A
Cited By
Fiber-reinforced high-strength medium-conductivity Cu-Ti alloy and preparation method and application thereof
CN120290997A
Method for preparing CuTi alloy strip based on ultrasonic-assisted solidification and liquid nitrogen cold rolling
CN120519730A